UPAYA GURU DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA DI SD RABBANI BANDUNG - Maulana, Arliansyah; Andewi Suhartini; Anisah Fitri Melenia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to investigate teachers' efforts in enhancing students' memorization of the Qur'an at Rabbani Bandung Elementary School. The type of research conducted is qualitative research with a case study approach, where data collection is carried out using observation, interviews, and documentation techniques. The findings reveal that teachers' efforts in improving students' Qur'an memorization at Rabbani Bandung Elementary School include grouping students based on their memorization abilities, managing the time for Tahfidz Program implementation, employing the Talaqqi method, and providing motivation for Qur'an memorization. In this study, it can be concluded that the teachers at Rabbani Elementary School in Bandung have implemented several effective efforts to enhance students' memorization of the Qur'an. Key efforts include grouping students according to their memorization abilities, effective time management, using the Talaqqi method, conducting muroja'ah, and offering motivation. This approach helps create a supportive learning environment to achieve the set memorization targets, emphasizing comprehension and appreciation of the Qur'an while fostering strong intention and motivation among students.